Early and Late Life - Bulge-Dominated Galaxies over the Last 8-9 Gyr. Issue Volume 11:Issue S319(2015) (17th August 2016) - Jørgensen, Inger; Chiboucas, Kristin; Bergmann, Marcel; Toft, Sune; Schiavon, Ricardo
Abstract: We present results from our investigation of galaxy evolution in dense cluster environments up to redshift z=1.3 based on high S/N ground-based spectroscopy and HST imaging of bulge-dominated galaxies: (1) An analysis of sizes, M/L ratios and line indices of galaxies in massive clusters out to z=1.3. The results are published in Jørgensen & Chiboucas (2013 ) and Jørgensen et al . (2014 ). (2) A preliminary analysis (Fig. 1) of absorption line indices, ages, metallicities and abundance ratios for galaxies in nine massive clusters out to z=0.9. New data cover three clusters at z=0.2-0.5.